Legal Review of Settlement of Customary Land Disputes Through Mediation According to Positive Law - Agnes Monika Gultom; Hisar Siregar; Ria Juliana Siregar (PT FORMOSA CENDEKIA GLOBAL, 2025)
Resolving customary land disputes through mediation is a relevant approach in the context of Indonesian people who have a diversity of customs and cultures. This article aims to analyze the mediation mechanism as an alternative to resolving customary land disputes within the framework of Indonesian positivist law. This study uses normative juridical methods and empirical approaches with literature and literature studies. The results of the analysis show that mediation as part of the alternative dispute resolution (ADR) system has been regulated in various laws and regulations in Indonesia, including Supreme Court Regulation No. 1 of 2016 concerning Mediation procedures in Court. In the context of customary land, mediation allows the integration of customary law values with positive law, resulting in a more accommodating and fair solution for the parties to the dispute. However, the implementation of mediation at the practical level often faces obstacles, such as differences in the interpretation of customary law and lack of understanding of mediation by the parties. Therefore, it is necessary to strengthen the capacity of mediators, clearer recognition of customary law and the national legal system, as well as harmonization between customary law and positive law to increase the effectiveness of resolving customary land disputes through mediation.